Advances in adjunct therapy against tuberculosis: Deciphering the emerging role of phytochemicals. Issue 4 (5th August 2021) - Fatima, Samreen; Kumari, Anjna; Dwivedi, Ved Prakash
Abstract: Eastern countries are a major source of medicinal plants, which set up a rich source of ethnopharmacologically known medicines used in the treatment of various diseases. These traditional medicines have been known as complementary, alternative, or nonconventional therapy across globe for ages. Tuberculosis (TB) poses a huge global burden and leads to maximum number of deaths due to an infectious agent. Treatment of TB using Directly Observed Treatment Short‐course (DOTS) therapy comprises multiple antibiotics is quite lengthy and causes serious side‐effects in different organs. The length of the TB treatment leads to withdrawal from the patients, which paves the way for the emergence of drug resistance in the bacterial population. These concerns related to therapy need serious and immediate interventions. Traditional medicines using phytochemicals has shown to provide tremendous potential in TB treatment, mainly in the eradication of Mycobacterium tuberculosis ( M.tb ), increasing natural immunity, and managing the side effects of anti‐TB drugs. This review describes the antituberculosis potential of selected ethnopharmacologically important phytochemicals as potential immune‐modulator and as an adjunct‐therapy in TB. This review will be a useful reference for researchers working on ethnopharmacology and will open the door for the discovery of novel agents as an adjunct‐therapy to tuberculosis. Abstract : The different modes of action of phytochemicals in adjunct therapy for the treatment of TB.